Towards Improved Industrial Relations of Employees in Ethiopian Agricultural Research Institute: The Case of Ambo Plant Protection Research Center, Ambo, Ethiopia (American Journal of Humanities and Social Sciences, 2015)
Industrial relations cover all such relationships that a business enterprise maintains with various sections of the society such as workers, state customers, and public who come into its contact. In other words, it is the study of the interactions among industry, its employees and the governments that oversee them. The general objective of the study is to assess the industrial relations of employees of Ambo Plant Protection Research Center (APPRC) and propose strategic measures for its improvement. The study employed comprehensive data collection methods whereby both secondary and primary methods of data collection methods were employed to address the objectives of the study. Data collected through structured questionnaire were analyzed with the help of simple descriptive statistics like frequencies and percentages and inferential statistics with the help of SPSS software (version 20). Promoting good governance and democracy, creating favorable working environment for employees and environment of good will and mutual cooperation, responding to employees’ reported problems promptly and positively; provision of trainings to employees on strategic issues and solutions; and encouraging employees to use modern technologies like ICTs in service delivery are some of the strategic measures proposed to improve the industrial relations of employees of Ambo Plant Protection Research Center.